2018
DOI: 10.1088/1361-6560/aad519
|View full text |Cite
|
Sign up to set email alerts
|

A simple B 1 correction method for dynamic contrast-enhanced MRI

Abstract: The double-angle method (DAM) is commonly used as a reference standard in radiofrequency field (B ) mapping studies. This study explored two aspects of DAM: (i) use of small flip angle pairs to reduce the repetition time (TR) needed for adequate longitudinal relaxation (T); and (ii) the effect of using different flip angle ratios for B mapping. Results of phantom studies show that B correction using small flip angle pairs ≤ 60° with TR  =  5000 ms can allow for accurate estimation of T up to about 1500 ms; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the present study, the DAM B 1 maps shown in figure 7(b) were acquired using the same 3D-SPGR sequence implemented for VFA imaging, but over a coarser acquisition matrix (64 × 64) and with a prolonged TR of 5000ms for in vivo B 1 imaging. For gray and white matter tissues with T 1 ranging from ∼800-1500ms, a prolonged TR of 5000ms ( 3 × 1500ms) used for DAM B 1 mapping would be adequate to remove residual T 1 effects in the B 1 images (Li et al 2018). However, regions with cerebrospinal fluid (CSF, such as the ventricles) that are associated with higher T 1  2500ms would require an even longer TR in order to yield accurate B 1 estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the DAM B 1 maps shown in figure 7(b) were acquired using the same 3D-SPGR sequence implemented for VFA imaging, but over a coarser acquisition matrix (64 × 64) and with a prolonged TR of 5000ms for in vivo B 1 imaging. For gray and white matter tissues with T 1 ranging from ∼800-1500ms, a prolonged TR of 5000ms ( 3 × 1500ms) used for DAM B 1 mapping would be adequate to remove residual T 1 effects in the B 1 images (Li et al 2018). However, regions with cerebrospinal fluid (CSF, such as the ventricles) that are associated with higher T 1  2500ms would require an even longer TR in order to yield accurate B 1 estimates.…”
Section: Discussionmentioning
confidence: 99%
“…While VFA methods (with no B 1 correction) have been found to yield either lower (Deoni 2007, Cheng and Wright 2006, Li et al 2018 or higher (Stikov et al 2015) T 1 estimates than IR in aqueous phantoms, VFA T 1 estimates were consistently higher than those measured by IR for in vivo studies (Stikov et al 2015). The exact reason for this observation is unclear and one could speculate that factors which may be greater in vivo than in phantoms, such as diffusion anisotropy, tissue conductivity and multiple-pool magnetization transfer, could result in the observed discrepancies between phantom and in vivo measurements (Stikov et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some drawbacks, VFA is still one of the most widely used T1 mapping methods in research. Its rapid acquisition time, rapid image processing time, and widespread availability makes it a great candidate for use in other quantitative imaging acquisition protocols like quantitative magnetization transfer imaging (Cercignani et al, 2005;Yarnykh, 2002) and dynamic contrast enhanced imaging (Li et al, 2018;Sung et al, 2013).…”
Section: Benefits and Pitfallsmentioning
confidence: 99%